The effects of preoperative focused cardiac ultrasound in high‐risk patients: A randomised controlled trial (PREOPFOCUS). Issue 10 (29th August 2022) - Pallesen, Jan; Bhavsar, Rajesh; Fjølner, Jesper; Bakke, Skule Arnesen; Krog, Jan; Andersen, Mikkel Andreas Strømgaard; Bøndergaard, Michael Helbo; Jessing, Thomas Damgaard; Mortensen, Lone; Nielsen, Michael Bugge; Vang, Marianne; Malachauskiené, Laima; et al.
Abstract: Background: Surgery is the third most common cause of mortality worldwide. Focused cardiac ultrasound (FOCUS) yields information on cardiac status and discloses the presence of unknown pathology. Preoperative FOCUS changes patient treatment, allowing for a patient‐tailored anaesthesia. We hypothesised that preoperative FOCUS would reduce the proportion of patients who were either admitted to hospital for more than 10 days or who were dead within 30 days after high‐risk, non‐cardiac surgery. Methods: This was a randomised, controlled, multi‐center study. Patients ≥65 years of age, admitted for urgent orthopaedic‐ or abdominal surgery, scheduled for general‐ or neuraxial anaesthesia and with ASA 3/4 were eligible for inclusion. Patients were randomised in a 1:1 ratio to preoperative FOCUS or no preoperative FOCUS performed in accordance with a predefined protocol. Primary endpoint was the proportion of patients admitted more than 10 days or who were dead within 30 days. Secondary endpoints included major complications, days of admission and changes in anaesthesia handling. Results: During the second COVID‐19 wave the study monitoring committee terminated the study prematurely. We included 338 patients of which 327 were included in the final analysis. In the FOCUS group, 41/163 (25%) patients met the criteria for the primary endpoint versus 35/164 (21%) for the control group, adjusted odds ratio 1.37 (95% CI 0.86–2.30), p  = .36. The proportions of patients who developed major complications did not differ significantly between groups. Length of hospital stay was 4 (3–8) days in the FOCUS group and 4 (3–7) days on the control group (adjusted p  = .24). Conclusion: The routine availability of preoperative FOCUS assessment in this cohort does not appear to reduce the risk for hospitalisation exceeding 10 days or 30‐day mortality, although study enrolment was prematurely terminated.